Confirmatory factor analysis of Post-Occupancy Evaluation Model (POEM) for sustainable neighborhood development - Yaman, Rostam; Thadaniti, Suwattana; Abdullah, Jamalunlaili; Ahmad, Noraini; Mohamed Ishak, Norishahaini (Institute of Physics Publishing, 2018)
The sustainable urban development growth in the ASEAN region has accelerated tremendously. More demand on the sustainable development has led to bigger market driven certified green neighborhood and buildings. However, there is a lack of post-occupancy evaluation study conducted in assessing the end-users perspective on the certified sustainable neighborhood development. This paper aims to investigate the end-users point of view on sustainable dimension pillar (SDP) adaptation based on environment dimension, social dimension and economic dimension using Post-Occupancy Evaluation Model (POEM) framework. The research methodology employed stakeholders-Inclusion Approach survey questionnaires in order to obtained the sustainable dimensional adaptation score. The results show that there is sustainable dimension gap in POEM evaluation, hence, suggested the pre- occupancy criteria did not fulfill the SDP adaptation and pre-occupancy criteria and variables if differ from post-occupancy criteria and variables.